(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The trend of associating with a celebrity for brand promotion has enraptured towards promoting tourism destinations. This paper tries to analyse the impact of celebrity endorsement as an efficient selling tool for on-line travel industry. The objectives framed to succeed in to the present goal were to spot whether or not the consumers take into account the tourism advertisements that are promoted by celebrities and to work out whether or not the employment of celebrities and its quality have a big impact on consumer’s purchase intention. The survey was done on 268 respondents of Delhi-NCR through a structured questionnaire using convenience sampling. The statistical tools such as SPSS, one sample t-test and AMOS have been applied for hypothesis testing. One Sample Wilcoxon Signed Rank test and Structural Equation modelling (SEM) is applied as a test of statistics. The outcomes of the study justified the application of TEARS model in tourism and online travel service industry in India. The foremost findings from the study were that the respondents solely get whole recognition and recall of the destination once the advertising is done by a celebrity endorser; it has been found that celebrity endorsers are more convincing and persuasive in better choice makings.